2018
DOI: 10.3802/jgo.2018.29.e25
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adjuvant hysterectomy on prognosis in patients with locally advanced cervical cancer treated with concurrent chemoradiotherapy: a meta-analysis

Abstract: ObjectiveFew data exist regarding adjuvant hysterectomy (AH) in locally advanced cervical cancer (LACC) patients treated with chemoradiotherapy. We investigated the effect of AH on prognosis in LACC patients, through meta-analysis.MethodsEMBASE and MEDLINE databases and the Cochrane Library were searched for published studies comparing LACC patients who received AH after chemoradiotherapy with those who did not, through April 2016. Endpoints were mortality and recurrence rates. For pooled estimates of the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 44 publications
0
46
0
2
Order By: Relevance
“…Hysterectomy is one of the most widely adopted therapeutic approaches for managing patients with early‐stage CC, along with concurrent radiation and chemotherapy (Johansen et al , ; Ross Green et al , ). However, majority of CC treatment protocols confer to a poor prognosis in patients, particularly in those who underwent hysterectomy (Shim et al , ). The molecular underpinnings of CC are not yet well elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Hysterectomy is one of the most widely adopted therapeutic approaches for managing patients with early‐stage CC, along with concurrent radiation and chemotherapy (Johansen et al , ; Ross Green et al , ). However, majority of CC treatment protocols confer to a poor prognosis in patients, particularly in those who underwent hysterectomy (Shim et al , ). The molecular underpinnings of CC are not yet well elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, salvage HT is a treatment speci cally for patients in whom tumors persist after de nitive RT/CCRT, whereas completion HT/adjuvant HT can be given to all patients who undergo de nitive RT/CCRT. A meta-analysis has shown that completion HT/adjuvant HT is not superior to conventional surveillance with regard to survival bene t [25]. Therefore, the selection of HT after de nitive RT/CCRT requires a careful patient selection strategy in order for it to be an effective treatment modality.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the rst to take the treatment intensity of RT into account when evaluating the e cacy of surgical treatment for cervical cancer after de nitive RT. Indeed, previous studies, including prospective trials or meta-analysis, did not contain details of RT intensity [20][21][22][23][24][25][27][28], which might preclude the adoption of salvage HT after de nitive RT/CCRT in the clinic. In the current study, the median dose of EQD2 in the HT cohort was 68.1 Gy, and this dose would ensure that RT/CCRT leads to a complete cure.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the rst to take the treatment intensity of RT into account when evaluating the e cacy of surgical treatment for cervical cancer after de nitive RT. Indeed, previous studies, including prospective trials or meta-analysis, did not contain details of RT intensity [20][21][22], which might preclude the adoption of salvage HT after de nitive RT/CCRT in the clinic. In the current study, the median dose of EQD2 in the HT cohort was 68.1 Gy, and this dose would ensure that RT/CCRT leads to a complete cure.…”
Section: Discussionmentioning
confidence: 99%